MHD mixed convection and entropy generation of nanofluid filled lid driven cavity under the influence of inclined magnetic fields imposed to its upper and lower diagonal triangular domains - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Chamkha, Ali J. (Elsevier, 2016)
In this study, mixed convection of CuO-water nanofluid filled lid driven cavity having its upper and lower triangular domains under the influence of inclined magnetic fields is numerically investigated. The top horizontal wall of the cavity is moving with constant speed of u(w) with +x direction while no-slip boundary conditions are imposed on the other walls of the cavity. The top wall of the cavity is maintained at constant cold temperature of T-c. while the bottom wall is at hot temperature of T-h and on the other walls of the cavity are assumed to be adiabatic. The governing equations are solved by using Galerkin weighted residual finite element formulation. Entropy generation is produced by using formulation and integrated with calculated velocities and temperatures. The numerical investigation is performed for a range of parameters: Richardson number (between 0.01 and 100), Hartmann number (between 0 and 50), inclination angle of magnetic field (between 0 degrees and 90 degrees) and solid volume fraction of the nanofluid (between 0 and 0.05). Different combinations of Hartmann numbers and inclination angles of the magnetic fields are imposed in the upper and lower triangular domains of the square cavity. It is observed that the local and averaged heat transfer deteriorates when the Richardson number, Hartmann number of the triangular domains increase. When the Hartmann number and magnetic angle of the upper triangle are increased, more deterioration of the averaged transfer is obtained when compared to lower triangular domain. Local and averaged heat transfer increase as the solid volume fraction of the nanoparticles increases and adding nanoparticles is more effective for the local enhancement of the heat transfer when the heat transfer rate is high and convection is not damped with lowering the Hartmann number. Second law analysis of the system for different combinations of flow parameters is also performed. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Inclined MHD flow; Different domains; Lid driven cavity; Nanofluids; Finite element method